2022
DOI: 10.3390/foods11030453
|View full text |Cite
|
Sign up to set email alerts
|

A Consumer Segmentation Study of Nutrition Information Seeking and Its Relation to Food Consumption in Beijing, China

Abstract: The aim of this study is to identify consumer groups based on nutrition information-seeking behavior and how it relates to food consumption. Although the Chinese public can now access nutrition information through different channels, research on the segmentation of homogeneous consumer groups seeking nutrition information is lacking. This study closes this research gap and, in doing so, also shows how information seeking is related to dietary behavior. A questionnaire was sent out to a stratified random sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…During the COVID-19 pandemic lockdown, Chinese consumption of salty snacks and alcoholic beverages declined statistically by 2.9% and 2.4%, respectively. This study confirmed the idea that during the pandemic lockdown, Chinese people emphasized nutrition and food-based dietary guidelines, which was consistent with other findings (e.g., [ 22 , 24 ]). Individuals can develop and maintain healthy eating habits, stay physically fit, and even lower their risk of underlying diseases, such as obesity and cardiovascular disease, by consuming adequate amounts of dietary fiber, vitamins, and minerals (i.e., fruits and vegetables) and limiting their intake of sugary beverages (by replacing them with sugar-free beverages) [ 7 , 9 , 16 , 19 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…During the COVID-19 pandemic lockdown, Chinese consumption of salty snacks and alcoholic beverages declined statistically by 2.9% and 2.4%, respectively. This study confirmed the idea that during the pandemic lockdown, Chinese people emphasized nutrition and food-based dietary guidelines, which was consistent with other findings (e.g., [ 22 , 24 ]). Individuals can develop and maintain healthy eating habits, stay physically fit, and even lower their risk of underlying diseases, such as obesity and cardiovascular disease, by consuming adequate amounts of dietary fiber, vitamins, and minerals (i.e., fruits and vegetables) and limiting their intake of sugary beverages (by replacing them with sugar-free beverages) [ 7 , 9 , 16 , 19 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Eight standard questions about information sources for food guidance and regularity of getting trustworthy recommendations for a healthy diet were used to gauge the effectiveness of food advice [ 24 , 27 , 35 ]. Each item was scored on a 7-point Likert scale (1 = never; 7 = always needed/wanted).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased urbanization and the rapid growth of the Chinese middle-income group have unprecedentedly changed their purchasing attention, particularly in food quality, nutrition, and food safety [1][2][3]. Today, consumers are fully aware of the effects of excessive pesticides and chemical fertilizer use on food crops [4].…”
Section: Introductionmentioning
confidence: 99%